John Wayne, The ultimate Collection (Legends, ,, 2009)
A collection of 25 digitally remastered John Wayne movies.
Disc 1 : Blue steel (54 min.) --, Dawn rider (55 min.) --, Desert trail (55 min.) --, Lawless frontier (50 min.) --, Lucky Texan (55 min.) --, Man from Utah (52 min.) --, Star packer (55 min.) --, Trail beyond (55 min.)., Disc 2 : Hell town (57 min.) --, Neath the Arizona skies (55 min.) --, Paradise canyon (53 min.) --, Rainbow valley (47 min.) --, Riders of destiny (53 min.) --, Sagebrush trail (55 min.) --, Texas terror (52 min.) --, Winds of the wasteland (56 min.)., Disc 3 : Randy rides alone (53 min.) --, West of the divide (53 min.) --, Angel and the badman (100 min.) --, McLintock (128 min.) --, American west of John Ford (52 min.)., Disc 4 : Shadow of the eagle (209 min.) --, Hurricane express (80 min.) --, Desert command (71 min.) --, His private secretary (60 min.).

Texas Rangers: Dead Man (Miramax double feature, ,, 2011)
Texas Rangers: In 1875, after the Civil War, Leander McNelly organizes the Texas Rangers to battle the outlaws terrorizing Texas, notably crime kingpin John King Fisher. With a team of experienced gunmen and enthusiastic but green recruits, McNelly and his Rangers bring law and order to the wild Texas plains. McNelly must also keep order among his charges when two rangers fall in love with the same woman. Dead Man: Johnny Depp (CHOCOLAT) delivers a remarkable performance in this highly acclaimed tale of adventure and intrigue in the wild, wild west! A young man in search of a fresh start, William Blake (Depp) embarks on an exciting journey to a new town ... never realizing the danger that lies ahead. But when a heated love triangle ends in double murder, Blake finds himself a wanted man, running scared -- until a mysterious loner teaches him to face the dangers that follow a "dead man."
Texas Rangers / directed by Steve Miner (90 min.) , Dead man /written and directed by Jim Jarmusch (121 min.), Dimension Films presents a Price Entertainment/Greisman production in association with Larry Levinson Productions, Inc., a Steve Miner film ; producers, Alan Greisman, Frank Price ; writers, Scott Busby, Martin Copeland ; director, Steve Miner.

To kill a mockingbird (Universal, 2006)
Gregory Peck plays a southern lawyer who defends a black man accused of rape in this film version of the Pulitzer Prize-winning novel. The way in which it captures a time, a place, and above all, a mood, makes this film a masterpiece. Experience one of the most significant milestones in film history like never before with To Kill a Mockingbird 50th Anniversary Edition. Screen legend Gregory Peck stars as courageous Southern lawyer Atticus Finch - the Academy Award winning performance hailed by the American Film Institute as the Greatest Movie Hero of All Time. Based on Harper Lees Pulitzer Prize winning novel about innocence, strength and conviction and nominated for 8 Academy Awards, this beloved classic is now digitally remastered and fully restored for optimum picture and sound quality and boasts hours of unforgettable bonus features. Watch it and remember why "its a sin to kill a mockingb
Disc 1: The film ; Bonus features: Academy Award best actor acceptance speech; American Film Institute Life Achievement Award; excerpt from Academy Tribute to Gregory Peck; Scout remembers; feature commentary with director Robert Mulligan and producer Alan Pakula; theatrical trailer; production notes. , Disc 2: A conversation with Gregory Peck / film by Cecilia Peck [et al.] ; produced & directed by Barbara Kopple (1999 ; 97 min.) ; Fearful symmetry: the making of To kill a mockingbird / a film by Charles Kiselyak. (1998 ; 90 min.)

John Wayne : the tribute collection (Mill Creek Entertainment, 2009)
A collection of 25 digitally remastered John Wayne movies.
Disc 1 : Blue steel (54 min.) , The dawn rider (55 min.) , The desert trail (55 min.) , The lawless frontier (50 min.) , The lucky Texan (55 min.) , The man from Utah (52 min.) , The star packer (55 min.) , The trail beyond (55 min.)., Disc 2 : Hell town (57 min.) , 'Neath the Arizona skies (55 min.) , Paradise canyon (53 min.) , Rainbow valley (47 min.) , Riders of destiny (53 min.) , Sagebrush trail (55 min.) , Texas terror (52 min.) , Winds of the wasteland (56 min.)., Disc 3 : Randy rides alone (53 min.) , West of the divide (53 min.) , Angel and the badman (100 min.) , McLintock (128 min.) , The American west of John Ford (52 min.)., Disc 4 : Shadow of the eagle (209 min.) , The hurricane express (80 min.) , Desert command (71 min.) , His private secretary (60 min.).

Great cinema: 15 films (TGG Direct, TGG Direct, LLC, 2010)
Snows of Kilimanjaro: Writer Harry Street reflects on his life as he lies dying from an infection while on safari in the shadow of Mount Kilimanjaro. Anna Karenina: A married woman finds true love in a man who isn't her husband. Connecticut Yankee in King Arthur's court: A young man dreams, after reading Mark Twain's classic novel of the same title, that he himself travels to King Arthur's court. Tale of two cities: A British barrister falls in love with a comely French lass who marries another. When her husband returns to Paris to rescue a family retainer he himself is imprisoned. The barrister then comes up with a daring plan to save the lass's husband. Jane Eyre: An orphan girl finds her way in life as a governess. Legend of the Sea Wolf: Chronicles the adventures on the high seas. Adventures of Huckleberry Finn: A rambunctious boy adventurer chafing under the bonds of civilization, escapes his humdrum world and his selfish father by sailing a raft down the Mississippi river. Jungle book: A boy raised by wolves tries to adapt to human village life. Call of the wild: A house dog is abducted and brought to the north as a sled dog. Macbeth: A ruthlessly ambitious Scottish lord seizes the throne with the help of his scheming wife and a trio of witches. Of human bondage: A man falls for a woman of loose morals. He rescues her a couple of times only to have her destroy his financial security. Little men: A young man finds refuge in a school for boys. His father is a con man. One of the teachers defends the boy when he is falsely accused and his father schemes to save the school from foreclosure. Last time I saw Paris: Charles returns to Paris to reminisce about his life he led in Paris after it was liberated. David Copperfield: Charles Dickens's immortal story of a young man's journey to maturity. Cyrano de Bergerac: The charismatic swordsmen-poet helps another to woo the woman he loves in this straightforward version of the play.
Disc 1 A. The snows of Kilimanjaro (1952) --, Anna Karenina (1948) --, A Connecticut Yankee in King Arthur's court (1952) --, Tale of two cities (1953) --, Disc 1 B. Jane Eyre (1971) --, Legend of the Sea Wolf (1975) --, Adventures of Huckleberry Finn (1953) --, Jungle book (1942)., Disc 2 A. Call of the wild (1972) --, Macbeth (1961) --, Of human bondage (1934) --, Little men (1940) --, Disc 2 B. The last time I saw Paris (1954) --, David Copperfield (1970) --, Cyrano de Bergerac (1950).

Shark tale (DreamWorks Home Entertainment, 2005)
Oscar is a lowly tongue-scrubber at the local Whale Wash, who becomes an improbable hero when he tells a great white lie. To keep his secret, Oscar teams up with an outcast vegetarian Great White shark, Lenny, and the two become the most unlikely of friends. When his lie begins to unravel, it's up to Oscar's loyal friend Angie and Lenny to help him stand up to the most feared shark in the water and find his true place in the reef.
MPAA rating: PG; for some mild language and crude humor.

Rio (20th Century Fox Home Entertainment, 2015)
"Blu es una exótica ave mascota que piensa que es el último de de su especie. Sin embargo, cuando su dueña se entera de la existencia de Perla, una hembra como Blu, en Río de Janiero, emprenden la aventura de sus vidas."--envase. A comedy-adventure that centers on Blu, a flightless macaw who acts more human than bird. When Blu, the last of his kind, discovers there's another, and that she's a she, he embarks on an adventure to magical Rio. There he meets Jewel and a menagerie of vivid characters who help Blu fulfill his dream and learn to fly.

Penguins of Madagascar (20th Century Fox Home Entertainment, Dreamworks Animation SKG Home Entertainment, 2009)
They're cute. They're cuddly. They're back! From the creators of "Madagascar" comes the hilarious new movie that proves global espionage is for the birds! In DreamWorks' "Penguins Of Madagascar," your favorite super-spies - Skipper, Kowalski, Rico and Private - join forces with the elite North Wind team to save the world. It's a side-splitting, globe-trotting adventure the whole family will love.
Popcorn panic --, Gone in a flash.

The Family Man (Universal Studios, 2001)
Jack Campbell, a workaholic Wall Street exec, gets to see what his life might have been like if he'd stayed with his former sweetheart, Kate. Thirteen years after they split up, Jack falls asleep in his posh New York apartment, then awakens to find himself a family man, with his now-wife Kate, daughter Annie and new baby.
Feature commentary with producer Marc Abraham --, Music score commentary with composer Danny Elfman --, Deleted scenes --, Outtakes --, Hi Jack Montage --, Music video: Seal "This could be heaven" --, Choose your fate game --, Production notes. Univeral Pictures and Beacon Pictures present a Riche/Ludwig-Zvi Howard Rosenman and Saturn production ; produced by Zvi Howard Rosenman, Tony Ludwig, Alan Riche, and Marc Abraham ; written by David Diamond and David Weissman ; directed by Brett Ratner., Cast & filmmakers , Languages: English 5.1 surround ; English dts 5.1 surround ; French Dolby surround , Captions: English , DVD-ROM features., Feature commentary with producer Marc Abraham --, Music score commentary with composer Danny Elfman --, Deleted scenes --, Outtakes --, Hi Jack Montage --, Music video: Seal "This could be heaven" --, Choose your fate game --, Production notes.

Paddington (Anchor Bay Entertainment, 2015)
Paddington tells the story of the comic misadventures of a young Peruvian bear who travels to London in search of a home. Finding himself lost and alone, he begins to realize that city life is not all he had imagined until he meets the kindly Brown family who read the label around his neck that says "Please look after this bear. Thank you," and offer him a temporary haven. It looks as though his luck has changed until this rare talking bear catches the eye of a museum taxidermist.

A dog's way home (Sony Pictures Home Entertainment, 2019)
As a puppy, Bella finds her way into the arms of Lucas, a young man who gives her a good home. When Bella becomes separated from Lucas, she soon finds herself on an epic, 400-mile journey to reunite with her beloved owner. Along the way, the lost but spirited dog touches the lives of an orphaned mountain lion, a down-on-his-luck veteran and some friendly strangers who happen to cross her path.

Heaven's fire (York Entertainment, 2001)
During an attempted robbery at the treasury building, Dean (Eric Roberts) finds himself pitted against former co-worker Quentin (J©ơrgen Prochnow) who is bent on stealing U.S. currency engraving plates. When Dean foils the getaway, two earthshaking explosions rock the high rise, trapping the robbers and a group of tourists inside. Dean tries to save the victims while keeping his foe at bay.

Deep impact (Parimount Home Entertainment, Amblin Entertainment, Paramount Pictures, DreamWorks LLC, 2009)
'Deep Impact' is the story of the world's reaction to a death sentence. As a comet approaches the earth which might not be destroyed or divertedbefore it reaches earth, each individual struggles in the face of extinction to find what most matters to him or her.
Paramount Pictures and Dreamworks Pictures present ; produced by Richard D. Zanuck, David Brown ; written by Bruce Joel Rubin and Michael Tolkin ; directed by Mimi Leder.

Garfield: The Movie (20th Century Fox Home Entertainment, 2004)
Garfield's owner, Jon, takes in sweet, but dimwitted pooch Odie, turning Garfield's perfect world upside-down. Now Garfield wants only one thing: Odie out of his home and his life! But when the hapless pup disappears and is kidnapped by a nasty dog trainer, Garfield, feeling responsible, tears himself away from the TV and springs into action.
Twentieth Century Fox presents a Davis Entertainment Company production.

Mud (Lionsgate, 2013)
Two boys, Ellis and his best friend Neckbone, find a mysterious man named Mud hiding out on a deserted island in the Mississippi. Mud tells the boys fantastic stories about his life, including how he killed a man in Texas and vengeful bounty hunters are coming to get him. He says he is planning to meet and escape with the love of his life, Juniper. The boys agree to help him, but it isn't long until their small town is besieged by bounty hunters out for blood.

Legends Of The Fall (Tristar Pictures, Inc, 2005)
The three sons of a retired army colonel in Montana struggle to keep their bond together as they all fall in love with the same woman.

The Secret of Roan Inish: Island of the Seals (1994)
A magical tale of a girl whose search for her missing brother brings an Irish legend to life.
Jones Entertainment Group Ltd. in association with Peter Newman Productions presents ; produced by Sarah Green, Maggie Renzi ; written for the screen [and] directed ... by John Sayles.

13 Going On 30 (Columbia TriStar Home Entertainment, 2004)
Jenna makes a wish on her 13th birthday to be 30 and grown up. When she wakes up the next day she finds herself, miraculously, just weeks away from her 30th birthday. The new, older Jenna is a successful magazine editor with friends in high places and a lion's share of potential suitors. The proplem is that her mind hasn't matured with her body and Jenna finds it a little more terrifying than cool to be living on her own.
Special features: Anamorphic widescreen , 18 deleted and extended scenes , Blooper reel , Two filmmaker audio commentaries , "I was a Teenage Geek" featurette , The Making of 13 Going on 30 , Pat Benatar's "Love is a battlefield" and Rick Springfield's "Jessie's Girl" music videos , "The 80's Outfit Challenge" set-top feature , "Then and Now" set-top feature , Language: English 5.1 Dolby digital ; French 5.1 Dolby digital , Subtitles: English, French., Revolution Studios presents a Roth/Arnold production, a Gina Matthews production ; produced by Gina Matthews, Susan Arnold and Donna Arkoff Roth ; written by Josh Goldsmith & Cathy Yuspa ; directed by Gary Winick.

Fever pitch (20th Century Fox Home Entertainment, 2005)
According to Red Sox super-fan Ben Wrightman, finding romance is about as likely as his beloved team winning the World Series. But when Ben scores a beautiful new girlfriend, suddenly anything is possible.
Break the curse --, Love Triangle --, Fox movie channel presents "Making A Scene."

Chicken Little (Walt Disney Home Entertainment, 2006)
Chicken Little causes widespread panic when he mistakes a falling acorn for a piece of the sky. After the fall out, the youngster becomes determined to restore his reputation . But just as things are starting to go his way, a real piece of the sky lands on his head. Chicken Little and his band of misfit friends, Abby Mallard (aka Ugly Duckling), Runt of the Litter and Fish Out of Water, attempt to save the world without sending the town into a whole new panic.
Special features: Deleted scenes with 3 alternate openings; "Hatching 'Chicken Little'": a making-of featurette; "Where's Fish!" interactive trivia game; The Cheetah Girls music video; Karaoke sing along; Barenaked Ladies music video. [presented by] Walt Disney Pictures ; produced by Randy Fullmer ; writers, Steve Bencich, Ron Friedman ; directed by Mark Dindal.